Determinants of cervical cancer screening via Pap smear among female staff in a tertiary hospital in Niger-Delta of Nigeria - Awoyesuku, Peter A.; Altraide, Basil O.; Mac Pepple, Dagogo A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cervical cancer remains a leading cause of death among women in the developing world, with poor prognosis attributed to lack of awareness about the disease and its prevention. Hospital workers’ attitude and practice to such an issue might positively or negatively influence people they come into contact with. This study is to assess the determinants of cervical cancer screening via Pap smear among Female Staff in a Tertiary Hospital in Nigeria. Methods: A hospital-based cross-sectional study was conducted between September and November 2015. A structured self-administered questionnaire was used to collect data from 265 female hospital workers on socio-demographic characteristics (age, parity, educational level and occupational category) and awareness and utilization of Pap smear test. The data obtained were analyzed using SPSS version 20.0. Results: Of the 265 respondents, only 40 (15.1%) had Pap smear test done at least once previously. Bivariate analysis of socio-demographic factors and Pap smear test uptake among the respondents was statistically significant for younger maternal age ≤35 years, not being married, higher educational level, professional occupation category and awareness of Pap smear. However, only maternal age, marital status and awareness of Pap smear remain statistically significant after multivariate analysis. Conclusions: Uptake of Pap smear test as a screening test for cervical cancer is low among female hospital workers. Identified determinants of cervical cancer screening via Pap smear test were younger age ≤35 years, not being married, higher educational level, professional occupational category and awareness of Pap smear.